Multicriteria spatial analysis applied to identifying ecosystem services in mixed-use river catchment areas in south central Chile - Carlos Esse; Rodrigo Santander-Massa; Francisco Encina-Montoya; Patricio De los Ríos; David Fonseca; Pablo Saavedra (Forest Ecosystems, 2019)
Abstract Background The flow of goods and services occurring in catchment areas allows the production of a series of ecosystem services. These have a direct impact on the inhabitants of the territory, who in turn recognise and value ecosystems (social value) as a function of the benefits which they generate. This has a direct impact on public policies that contribute to the development of local economies. The present study therefore sought to identify and recognize the social value of the various ecosystem services provided by a mixed-use catchment area in which different productive activities are concentrated. This study examined the social value of ecosystem services and offers qualitative or quantitative, non-monetary estimates of the relative importance of different benefits for human society derived from the functioning of ecosystems (Laterra et al, Valoración de Servicios Ecosistémicos, Conceptos, herramientas y aplicaciones para el ordenamiento territorial, 2011). The methodology involved the participation of leading actors in the territory, and a panel of experts who defined criteria and weighting which were applied to a multicriteria spatial model. They assigned ordinal scale to the territory representing levels of appreciation based on the various ecosystem services in the ecological, productive, landscape and cultural dimensions. The results showed that the inhabitants of the territory recognise the ecosystem benefit of areas covered by native forest, in particular the species Nothofagus dombeyi (Mirb.) Oerst., in contrast to areas used for farm production. The functioning of the ecosystem is recognised, and particularly its contribution to regulating water flows and to water production and quality. Results The study results showed that areas covered with secondary forest of N. dombeyi provide a variety of ecosystem functions which support the creation of ecosystem services to the population, especially in riparian areas throughout the basin where they are important for water production and quality. ES ponderations for provision, regulation and cultural showed that the native forest and riparian units (HEU 1 and HEU 6) as a very important group in relation to the ES because there are recognized by the local society (P < 0.05). The leading actors assigned a low social value to other land-uses, like mixed use and farmland, because of the high degree of anthropisation of these ecosystems; this viewpoint has generated conflicts in the territory. Neither foresters nor farmers recognise or accept the impacts of their activities on the various ecosystem services provided by the territories where they operate, even though they are leading actors for the development of local economies. Conclusion The participation of the leading actors of a territory, represented spatially in a multicriteria analysis model, highlighted the social value of the ecosystems present in a hydrographic catchment area which supports different productive and conservation activities. The model contributed to understanding of the functional processes which generate goods and services present in the physical medium. The study used a hybrid method which included definition of homogeneous environmental units and multicriteria and multivariate statistical analysis. This allowed the information provided by the actors in the territory to be analysed with different spatial scales, levels of perception and elements of territorial planning which contribute to the generation of public policies and the sustainable management and conservation of natural ecosystems.